Prevalence and overlap of known undernutrition risk factors in children in Nairobi Kenya - Antonina N. Mutoro; Ada L. Garcia; Elizabeth W. Kimani‐Murage; Charlotte M. Wright (Wiley, 2022)
Abstract We aimed to describe the co‐occurrence of known risk factors for undernutrition and the prevalence of modifiable risks in wasted, stunted and healthy children. Quota sampling was used to recruit healthy [weight for age Z scores (WAZ) > −2 SD] and undernourished [weight for length (WLZ) or WAZ scores ≤ −2 SD] children aged 6-24 months from seven clinics in low‐income areas of Nairobi. Structured interviews were used to identify exposure to socioeconomic, water and hygiene, infant feeding, dietary and behavioural risks (low interest in food, high food refusal and force feeding). We recruited 92 wasted WLZ ≤ −2 SD, 133 stunted (length for age Z scores LAZ ≤ −2 SD) and 172 healthy (LAZ and WLZ > 2SD) children. Nearly all children were exposed to hygiene risks (90%) and low dietary diversity (95%) regardless of nutritional status. Stunted children were more likely to be exposed to socio‐economic risks (54% healthy, 64% wasted and 72% stunted; P = 0.001). Compared with healthy children, wasted and stunted children were more likely to be exposed to infant feeding (25% healthy, 40% wasted and 41% stunted; P = 0.02) and behaviour risks (24% healthy, 49% wasted, and 44% stunted; P = 0.004). Overall, wasted and stunted children were twice as likely to be exposed to more than three risks (23% healthy, 48% wasted, and 50% stunted; P = <0.001). They were also more likely to be exposed to more than three modifiable risks (dietary, handwashing and behaviour risks). Wasting and stunting are associated with exposure to multiple risk factors, many of which are potentially modifiable using targeted advice.